2021
DOI: 10.1007/s12517-021-08308-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural styles of the Tellian fold-and-thrust belt of Tunisia based on structural transects: Insights on the subsurface oil and gas pre-salt plays

Abstract: We present several structural transects throughout the internal part of the Tunisian Tell focusing on some representative structures and domains. We used also an interpreted seismic crosssection and a 3-D structural view to highlight the styles within the Tellian Units in the Fernana-Adissa allochthon domain. The structural style is mainly represented by active roof-thrust and duplex structures affecting the Mesozoic-Cenozoic sequences belonging respectively to the Infra-Kasseb and Kasseb Units. The main decol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Subsequently, the extension seems to be accelerated and hyperactive subsidence prevailed during this episode which is correlated with the major extensional Tethyan tectonics (Soussi 2003) and/or the acceleration in the Central Atlantic opening (Guiraud et al 2005). From the late Jurassic to the Barremian, the sedimentation in the major northern part of Africa was still mostly guided by ~E-W normal fault systems, presumably related to major basement discontinuities inherited from the Triassic period (Piqué et al 2002;Khomsi et al 2004;De Lamotte et al 2009;Khelil et al 2021b). Accordingly, the Jurassic rifting induced a general northward block-tilting geometry along northern Tunisia basin (Soussi 2003).…”
Section: Cretaceous Geodynamic History Of the Northern Tunisiamentioning
confidence: 98%
“…Subsequently, the extension seems to be accelerated and hyperactive subsidence prevailed during this episode which is correlated with the major extensional Tethyan tectonics (Soussi 2003) and/or the acceleration in the Central Atlantic opening (Guiraud et al 2005). From the late Jurassic to the Barremian, the sedimentation in the major northern part of Africa was still mostly guided by ~E-W normal fault systems, presumably related to major basement discontinuities inherited from the Triassic period (Piqué et al 2002;Khomsi et al 2004;De Lamotte et al 2009;Khelil et al 2021b). Accordingly, the Jurassic rifting induced a general northward block-tilting geometry along northern Tunisia basin (Soussi 2003).…”
Section: Cretaceous Geodynamic History Of the Northern Tunisiamentioning
confidence: 98%
“…Mesozoic to Quaternary series outcrops in the study area (Figure 12). The study area Except the evaporitic Triassic Frontiers in Earth Science frontiersin.org deposits, corresponding to Lagoonal to marine subsiding epicontinental facies (Khelil et al, 2021), the Meso Cenozoic series are mostly clays and carbonates, with Oligocene sands to the top (Figure 13A). These formations are deposited in a marine environment.…”
Section: The Lower Mejerda Valley: Geological Backgroundmentioning
confidence: 99%
“…The Neogene and Quaternary sedimentation is characterized by continental/lagoonal fluvial deltaic environment, except the Pliocene open marine sediments (Figure 13B). The fluvial deltaic Kechabta formation is Very thick, reaching 1,200 m (El Euch-El Koundi et al, 2022), indicating important subsidence [Figure 14 (Bejaoui et al, 2017;Gaidi et al, 2020;Khelil et al, 2021)] during the Late Miocene, simultaneously to the docking of the Kabylies against Africa (Frizon De Lamotte et al, 2000;Frizon De Lamotte et al, 2009;Khomsi et al, 2016;Booth-Rea et al, 2018;Khomsi et al, 2019;Camafort Blanco et al, 2020;Khelil et al, 2021;El Euch-El Koundi et al, 2022). Recent work by El Euch-El Koundi et al (2022) on the Chaabet Tabela formation confirmed the importance of the tectonic activity, with the climate, controlling the alluvial fan deposits.…”
Section: The Lower Mejerda Valley: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These contrasting views of the Western Mediterranean nappe domains imply differences in crustal and lithospheric structure, age of extension, hydrocarbon prospectivity, amount and age of shortening, role of tectonic inversion, age and position of orogenic boundaries and tectonic mechanisms driving deformation in the region, among other features. For example, stratigraphic omissions observed in the lithological series of these nappe belt domains are related to erosion or salt welds according to the first hypothesis (e.g., Daudet et al, 2020;Khelil et al, 2021) or to extensional tectonic omissions by the latter (Booth-Rea et al, 2012, 2018Brogi, 2008;Crespo-Blanc & Campos, 2001;García-Dueñas et al, 1992;Moragues et al, 2021;Rodríguez-Fernández, Azor, & Azañón, 2011). Extensional faults cut down into the previous structure toward the sense of hanging-wall displacement producing lithological omissions in the stratigraphic sequence, including metamorphic gaps, with less metamorphic over higher-grade rocks, along crustal-scale extensional shear zones (e.g., Caby et al, 2001;Lonergan & Platt, 1995;Martínez-Martínez et al, 2002;Platt, 1986;Wernicke, 1981;Wernicke & Burchfiel, 1982).…”
mentioning
confidence: 99%